‘Communist Education Days’, the Indoctrination of Czechoslovak Communist Party Members in the 1948–1949: Organization, Ideological Background, and Local Practice - Kaška, Václav (Dějiny – teorie – kritika, 2008)
This article examines a form of Party training in Czechoslovakia called DKV (Dny komunistické výchovy – Communist Education Days). This programme of mass indoctrination of Czechoslovak Communist Party members after the Communist takeover in February 1948 ran from August 1948 and to June 1949. The article is more generally focused on the reconstruction of everyday life within the local Party networks. It first considers the formal aspects of the DKV. Here, Party members attended lectures on a topic of the month, familiarizing themselves with the basic doctrines of Marxism-Leninism. The article reconstructs the running of the DKV in Brtnice (in the Jihlava region) and Břežany (in the Znojmo region), demonstrating that the demands of Party headquarters were considerably adapted to local circumstances and that the whole operation ended up being not quite as intensive as Party headquarters had planned. The two local organizations considered in the article often preferred other, more urgent activities, to the ideological equipping of its members. When indoctrination eventually did take place there was not as much of it as Party headquarters had planned, nor was it of the quality they had anticipated.